Molecular beam epitaxy growth of MgZnSSe/ZnSSe Bragg mirrors controlled by in situ optical reflectometry. - HEGARTY, JOHN (My University, 1995)
In situ optical reflectometry at the wavelength of 488 nm was employed to control the growth of MgZnSSe/ZnSSe Bragg mirror stacks for the blue-green spectral region. 10- and 20-period layer structures of MgZnSSe/ZnSSe were grown on GaAs ~100! epilayers by molecular beam epitaxy. A room-temperature peak reflectance of 86% was obtained for the 20-period structure at the central wavelength of 474 nm. The results show that, in general, in situ optical monitoring of growth is a viable and simple method for real-time layer thickness control of MgZnSSe/ZnSSe quarter-wave stacks.
PUBLISHED
Keywords: Physics